Respostas
respondido por:
1
a) 7! + 6! = 7.6! + 6! = 6! (7 + 1) = 8.6!
8!/ 8.6! = 8.7.6!/8.6! corta 6! em cima e em baixo fica
8.7/8 = 7
b) 6! + 5! = 6.5! + 5! = 5! ( 6 + 1) = 7.5!
5! - 4! = 5.4! - 4! = 4!(5 - 1) = 4.4!
7 . 5! / 4 . 4! = 7.5.4!/4.4!
cancela 4! em cima e em baixo fica
7.5/4 = 35/4 = 8,7 (aproximadamente)
c)5.n! - (n-1)! = 5.n! - n.(n-1)!/n = 5.n! - n!/n = n! (5 - 1/n) = n!( 5n/n -1/n) = n! ( 5n/n -1/n)
n! ( 5n/n - 1/n) ÷ n! = 5n/n - 1/n = (5n - 1)/n
8!/ 8.6! = 8.7.6!/8.6! corta 6! em cima e em baixo fica
8.7/8 = 7
b) 6! + 5! = 6.5! + 5! = 5! ( 6 + 1) = 7.5!
5! - 4! = 5.4! - 4! = 4!(5 - 1) = 4.4!
7 . 5! / 4 . 4! = 7.5.4!/4.4!
cancela 4! em cima e em baixo fica
7.5/4 = 35/4 = 8,7 (aproximadamente)
c)5.n! - (n-1)! = 5.n! - n.(n-1)!/n = 5.n! - n!/n = n! (5 - 1/n) = n!( 5n/n -1/n) = n! ( 5n/n -1/n)
n! ( 5n/n - 1/n) ÷ n! = 5n/n - 1/n = (5n - 1)/n
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás